Antimicrobial Resistance Pattern of Extensively Drug Resistant Carbapenemase Producing Enterobacteriaceae - Afroz, Fatima; Anwar, Shaheda; Quraishi, Mashrura; Mohiuddin, GM; Ahmed, SM Ali; Saleh, Ahmed Abu (Bangladesh Journal of Medical Microbiology, 2019)
Carbapenems, often agents of last resort for multidrug resistant bacterial infections are now threatened by widespread dissemination of carbapenem-resistant Enterobacteriaceae (CRE). Production of carbapenemases remain the most clinically important mechanism of carbapenem resistance in Enterobacteriaceae. The objective of this study was to determine the antibiogram pattern of carbapenemase producing Enterobacteriaceae. A cross sectional study was conducted at department of Microbiology and Immunology, BSMMU from September 2018 to August 2019. A total of 145 CRE isolates from different clinical samples were studied.Antimicrobial susceptibility was examinedby disk diffusion method and MIC of colistin by broth microdilution method. Resistant carbapenemase genes NDM and OXA-48 were identified by polymerase chain reaction. Out of 145 CRE isolates, 104 were NDM, 73 were OXA-48and 34 isolates were both NDM and OXA-48 co-producers. All the NDM and OXA-48 carbapenemase producing isolates were 100% resistant to meropenem, imipenem, ertapenem, ceftriaxone, ceftazidime, cefotaxime, cefuroxime, amoxicillin + clavulanic acid and piperacillin + tazobactam. Resistance rates of reserved antimicrobials to treat CRE isolates were also alarming. Thirty seven percent, 9.6% and 5.5 % of OXA-48 carbapenemase producers and 26.0%, 10.6% and 2.9% of NDM carbapenemase producers were resistant to colistin, polymyxin B and tigecycline respectively.Among the carbapenemase producing isolates, 16.6% (24) were multidrug resistant (MDR), 82.1% (119) were extensively drug resistant (XDR) and 1.3% (2) isolates were pan drug resistantwhich highlights the emerging therapeutic challenge for these superbugs. Bangladesh J Med Microbiol 2019; 13 (2): 7-10